MATHPRO 5.0 / Siti Zaharah Mohd Ruslan and Norlida Othman - Mohd Ruslan, Siti Zaharah; Othman, Norlida (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The College of Computing, Informatics and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah has organized MATHPRO 5.0 on 6 January 2023 in association with Cybermath Club for MAT133 and MAT112 students. This program was attended by 149 students. The program was held between 2:00 pm to 5:00 pm. The purpose of this program was to increase students' interest in actively learning mathematics. All of the students, who were grouped into 15 teams, participated in the program's activities, which were conducted at five checkpoints. The organizers create games at each checkpoint to increase students' problem-solving and obstacle-handling skills. This program is intended to identify actions that can be taken to enhance student performance and lower the failure rate.